Inhibition Mechanism of Gosha-jinki-gan on the Micturition Reflex in Rats - Akinobu Gotoh; Kazuhiro Goto; Atsushi Sengoku; Toshiro Shirakawa; Yoshinobu Akao; Masato Fujisawa; Hiroshi Okada; Soichi Arakawa; Sadao Kamidono (Journal of Pharmacological Sciences, 2004)
We investigated the actions of Gosha-jinki-gan, a traditional Japanese medicine containing processed Aconiti tubers, on urinary bladder function in anesthetized rats. In cystometrical investigations, Gosha-jinki-gan (1.0 g/kg, i.d.) increased bladder capacity as well as micturition threshold pressure. In addition, it decreased the frequency of distension-induced rhythmic bladder contractions. However, it did not influence the amplitude of bladder contractions induced by electrical stimulation of the pontine micturition center. The inhibitory effect of Gosha-jinki-gan on bladder motility was abolished by pretreatment with nor-binaltorphimine (10 mg/kg, s.c.), and was diminished by the concomitant use of anti-dynorphin A antiserum (10 μg, i.t.), yohimbine (10 μg, i.t.), or methysergide (20 μg, i.t.). Processed Aconiti tuber extract (27 mg/kg, i.d.) also suppressed bladder motility, and the effect was abolished by nor-binaltorphimine. These results suggest that Gosha-jinki-gan attenuates bladder sensation via the kappa-opioid receptor-stimulating action of processed Aconiti tuber. Gosha-jinki-gan may be a useful anti-pollakiuria agent that does not influence bladder contractility at micturition. Keywords:: Gosha-jinki-gan, anti-pollakiuria effect, micturition reflex, kappa-opioid receptor, processed Aconiti tuber